Correlations of electrocardiographic changes in terms of anthropometric characteristics in athletes in the Republic of North Macedonia - Karagjozova, Ivanka; Pluncevikj Gligoroska, Jasmina; Nestorova Brazanska, Mihaela; Spirkoska Vangelovska, Biljana; Ristovski, Vangel; Georgievska-Ismail, Ljubica (Anthropological Society of Serbia, 2023)
Electrocardiographic (ECG) changes in athletes occur due to structural, functional and electric remodeling of the heart, as a direct result of their long-term engagement in sporting activities. The objective of this study was to establish a potential correlation of changes in the ECG pertaining to certain anthropometric characteristics. In this prospective cross-sectional study, conducted during 2016 and 2017, 285 athletes aged between 9 and 38 of both sexes were included. Anthropometric characteristics were determined on all the athletes alongside a 12-lead ECG. The average age of the respondents was 19.3±5.7. No significant correlation between the ECG characteristics and the athletes’ age was found (r = -0,009, p = 0,880). There was no significant difference in the percentage of borderline and abnormal changes of ECG in terms of sex, even though they were marginally higher in male athletes. The correlation research has shown that a normal ECG significantly correlates with females (r = -0,205, p = 0,001). The athlete subjects who had a normal ECG had a significantly shorter body height and marginally lower body weight compared to those with physiological changes in the ECG. The changes in ECG are related to the body height, weight and sex, which are most probably due to the lesser range of heart remodeling, as well as the rate of participation in sports that can contribute to ECG changes.